Math, asked by RisingStar1268, 1 year ago

show that : (63+49)+37=63+(49+37).

Answers

Answered by Anonymous
4

(63+49)+37=112+37=149

63+(49+37)=63+86=149

Therefore (63+49)+37=63+(49+37)

please mark as Brainliest....

and follow me...

Answered by setukumar345
0

Concept :

The sum of two or more figures is calculated by adding them all together, which is what the addition is. One of the four fundamental operations of mathematics is addition, which is typically denoted by the plus sign (+). The other three are subtraction, multiplication, and division. The exact amount or total of the two whole numbers is obtained by adding them. The addends in an additional problem are referred to as such, whereas the solution to the additional solution is referred to as the sum. Other names for addition include adding, total, sum, add, and merge.

Given:

(63+49)+37=63+(49+37)

Find:

We have to prove the equation.

Solution:

According to the problem,

(63+49)+37=63+(49+37)

L.H.S-

(63+49)+37=112+37=149

R.H.S-

63+(49+37)=63+86=149

Therefore, (63+49)+37=63+(49+37)

Hence (63+49)+37=63+(49+37) , the equation is proved

#SPJ2

Similar questions